OUT-OF-BODY EXPERIENCE, PURE BEING AND METAPHYSICS - I. V. Karivets (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The author will show that metaphysical concepts and the concepts of empirical sciences derive from experience. The only difference is that metaphysical concepts derive from unusual experience, i.e. out-of-body experience, while empirical sciences – from usual one. The example set metaphysical concept of pure being. Methodology. In order to obtain this goal the author uses two methods. The first one is comparative method. With the help of this method the stories of men who experienced clinical death and returned to life are compared with the famous philosophers’ metaphysical statements (Plato, Descartes, and Bonaventura). The second one is transpersonal method. It helps to study the peculiarities of the extraordinary experience in the state of clinical death or mystical ecstasy. Such experience lies in experience of transcendence, pure being as light, ultimate awareness of truth, which are identical to the metaphysical statements of philosophers and mystics. These ultimate experiences belong to different people, who lived and grown in different cultures, but nevertheless metaphysical statements of philosophers or mystics and statements of the ordinary people who experienced clinical death are the same. Therefore we can say that out-of-body experience is transpersonal. Originality. Metaphysics is neither speculative nor withdrawn from experience of a human being sphere. It arises from out-of-body experience while empirical sciences – from usual experience. Therefore, metaphysical concepts, in particular, pure being, are empirical, because they are based also on (extraordinary) experience. In general, metaphysics becomes possible on the basis of out-of-body experience. Conclusions. In this article the author argues that the concepts of metaphysics are not a priori because they originate from out-of-body experience that is from the experience of the distinction between body and soul or body and mind. As a result of such experience appear, for instance, Plato’s metaphysics, Descartes’ metaphysics, and the Christian mysticism of Bonaventure, which theoretical constructs are deriving from experience of pure being (light). In this context metaphysics is seen as the path of gradual separation of a human being from his or her physical body, i.e. “the art of dying” (Plato). Therefore, the author proves that there are no a priori concepts. All concepts are aposteriori, in empirical sciences and in metaphysics as well. We simply talk about two different experiences: usual and unusual experience. The author also argues that there is direct connection between out of body experience and metaphysics, mystics. In the case of out-of-body experience, the temporary death of a human being is the cause of his/her change in perception of himself/herself and the world; it is the cause of metaphysical knowledge.